FROM THE 1964 CABINET CRISIS TO THE 2014 CABINET IN MALAWI: - Q Jere (Acta Theologica)
There is always a reason behind a paradigm shift that takes place in society. The Presbyterian Church (CCAP) in Malawi is one of the religious institutions that played a critical role in the nation’s liberation and fight for independence. Seven weeks into independence a cabinet crisis occured where some ministers were dismissed, while others resigned in support of their fired colleagues. Ironically, the Church kept a low profile and did hardly anything to intervene. This article assesses how, in 1964, the cabinet crisis impacted on the role of the Church and argues that political conflicts influence relations between the Church and the State. Furthermore, the article contributes to the current debate on Church and State relations through the lenses of Calvin’s Church and State and the 1964 cabinet crisis. The article is informed by Calvin’s Church and State, with the focus on how this conceptual thought influences Church-State relations.